2022
DOI: 10.1108/tr-03-2022-0129
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Tourism – understanding blind and vision-impaired tourists’ behaviour towards inclusion

Abstract: Purpose The physiological and psychological issues that limit people with vision impairment make it difficult for them to participate in tourism activities and enjoy the various benefits of tourism. This study aims to construct a theoretical model of the tourism-influencing factors that can lead to problems for people with vision impairment to meet their travel desires and improve their enjoyment of life. Design/methodology/approach This study adopted a mixed-methods approach. A theoretical model of the tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 88 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…Moreover, tourist destinations should provide personalized information and content through touchscreen devices with braille, audio description in different languages and talk-to-text. These initiatives will encourage blind people and their families to enjoy the beaches (Qiao et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tourist destinations should provide personalized information and content through touchscreen devices with braille, audio description in different languages and talk-to-text. These initiatives will encourage blind people and their families to enjoy the beaches (Qiao et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Accessible tourism requires cooperation between many interested parties to enable blind people and those with other disabilities to commute independently (Buhalis et al , 2012). Accessible tourism must provide mobile, visual, auditory and mental accessibility for people with disabilities, so they can move independently, equally and with dignity during holidays (Popović et al , 2022; Qiao et al , 2023). A tourist destination’s accessibility must tackle appropriated information of accessible facilities for people with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…There are as many interpretations of the concept of AT as there are authors who have contributed to the subject (Darcy and Dickson, 2009; Devile and Kastenholz, 2018; Liasidou et al , 2022; Pasca et al , 2022; Qiao et al , 2023; Rahmafitria et al , 2023; Scheyvens and Biddulph, 2018; Thomas, 2018). Among them, the proposal by Darcy and Buhalis (2011) enjoys widespread acceptance:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, research on PwVIB's tourism experiences is scarce, as a systematic literature review by Noghan et al (2023) found only seven papers addressing the topic. While these studies provide insights on issues such as embodied experiences (Small et al, 2012;Richards et al, 2010), sensory aspects of the experience (Riofrio-Grijalva et al, 2020), intention to travel (Qiao et al, 2023a) and embodiment and sensory compensation (Qiao et al, 2023b), individually and collectively they fail to deliver a comprehensive explanation of how PwVIB form and perceive their tourist experience. Thus, a significant knowledge gap exists in terms of understanding the psycho-cognitive processes underlying how PwVIB experience, perceive and interpret tourism, preventing providers from designing appealing, relevant and experiential experiences.…”
Section: Introductionmentioning
confidence: 99%